Molecular Imaging of Myocardial Injury: A Magnetofluorescent Approach - Sosnovik, David E. (2009)
The role of molecular imaging in enhancing the understanding of myocardial injury and repair is rapidly expanding. Moreover, in recent years magnetic resonance and fluorescence-based approaches have been added to the molecular imaging armamentarium and have been used to image selected molecular and cellular targets in the myocardium. Apoptosis, necrosis, macrophage infiltration, myeloperoxidase activity, cathepsin activity, and type 1 collagen have all been imaged in vivo with a magnetofluorescent (MRI and/or fluorescence) approach. This review highlights the potential of these and other magnetofluorescent agents, with particular focus on their role in ischemic heart disease.